EVALUASI KINERJA SAMBUNGAN PROPELAN PADA MOTOR ROKET RX 550 [EVALUATION OF THE PROPELLANT JOINT PERFORMANCE IN ROCKET MOTOR RX 550] - Sutrisno (Indonesian Journal of Aerospace, 2012)
The propellant joints quality of RX 550 rocket motor using segmented HTPB propellant was become a debatable. In static test this rocket motor exploded and the nozzle was broken out at seven second after ignition. To evaluate these propellant joints the propellant installation in rocket motor was discused. The propellant joint strength was tested using Tensilon UTM III-100 test equipment. The rocket motor tube at the propellant joint position were marked and investigated before and after static test. The datas such as thrust and chamber pressure versus time were analyzed for finding the posibility of joints defect. Based on analysis it is found that the propellant joint can work well. The RX 550 rocket motor failure in static test didn’t caused by propellant joints.